PENGARUH KEBIJAKAN AREA TERHADAP KINERJA KARYAWAN PADA BANK BTPN MITRA USAHA RAKYAT AREA BOGOR - ., Jeffry (STIE Binaniaga, 2013)
Employee performance is crucial in any company to achieve what was to become the main purpose of the company. Performance within an organization should be done by all human resources in the organization either as a leader or as a worker. The performance of an employee would be good in having a high expertise, working in accordance with salaries and had good expectations in the future.The author does observation by using a questionnaire, which first performed testing of 20 respondents in Micro BTPN area, staff of 20 samples of respondents, conducted the test validity and reabilitas, there are four questions that are invalid on the policy factor, whereas in the performance factor, there is one question that is not valid. Invalid question, omitted from the questionnaire will be distributed back to all employees. Total overall received questionnaires and data processing is conducted as many as 118 respondents.The test results with the use of SPPS, the data from the 118 respondents, data is distributed normally, it can be seen from the results of testing against policy on a real level of 5% (0.486) and performance (0.094), test value is larger than the real extent, so that data is distributed normally. The correlation between test results policy (X) on performance (Y), showing the significance of the value 0.000 is smaller on the real extent of 1%, which means that there is a positive and significant relationship between policy and performance of employees. The better the policies that are applied, then the better the performance generated by the employees. The resulting Simple Linear Regression test the equation Y = 49.151 + 0.444 X factor, meaning that policy has a positive relationship with respect to employee performance, shown with variable coefficients marked a positive policy. Key Word : Wisdom, Performance